2001
DOI: 10.1159/000048861
|View full text |Cite
|
Sign up to set email alerts
|

Sensory and Biomechanical Responses to Distension of the Normal Human Rectum and Sigmoid Colon

Abstract: Background: Visceral pain is a major clinical problem. The aim of the present study was to compare the pain and biomechanical responses to standardized distension of the human colon. Methods: The relation between pain intensity and pressure, cross-sectional area (CSA) and tension-strain relations of the rectum and sigmoid colon were studied in 11 normal subjects following standardized distension using impedance planimetry. The bag was inflated stepwise with pressures up to 6 kPa. The subjects, who were blinded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
42
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 21 publications
3
42
0
1
Order By: Relevance
“…the fractional rectal filling relative to rectal capacity [(rectal capacity – measured volume)/rectal capacity]. Normalized rectal volume is a dimensionless parameter, analogous to strain measured by impedance planimetry [27,28]. This measurement is independent of variation in rectal capacity and, therefore, facilitates comparisons between patients [8].…”
Section: Methodsmentioning
confidence: 99%
“…the fractional rectal filling relative to rectal capacity [(rectal capacity – measured volume)/rectal capacity]. Normalized rectal volume is a dimensionless parameter, analogous to strain measured by impedance planimetry [27,28]. This measurement is independent of variation in rectal capacity and, therefore, facilitates comparisons between patients [8].…”
Section: Methodsmentioning
confidence: 99%
“…Rectal capacity and normalized rectal volume may provide useful information about rectal function that is complementary to conventional barostat measurements such as compliance. 7,9,10 Moreover, rectal capacity itself may provide a useful assessment of fecal reservoir function.…”
mentioning
confidence: 99%
“…However, L 0 has been derived by comparing the length-tension relationship before and after administration of smooth muscle relaxants. 9,10,13,14 Unfortunately, the administration of these agents is not practical in clinical assessment and the technique used in these studies, impedance planimetry, is technically difficult to perform. This study proposes that rectal capacity can be measured at high distention pressures.…”
mentioning
confidence: 99%
“…Immediately after filling of the bag, 50 ml of water at the desired temperature was recirculated without changing the volume or pressure in the bag. In pilot experiments, it was found that, during perfusion of the esophagus, temperatures inside the bag of ϳ5, 10,15,20,25,30,35,40,45, and 50°C corresponded with water temperatures of 0, 5, 10, 16, 22, 30, 35, 44, 52, and 60°C in the pump system. Similar to the electrical stimuli, we used a pseudorandom, blinded sequence with lower-intensity stimuli interspersed with the ascending stimulus intensities.…”
Section: Stimulation Device and Protocolmentioning
confidence: 98%
“…We used a protocol with pseudorandom sequences including lower-intensity stimuli interspersed with the ascending stimulus intensities. Such series have proven to be valuable in our previous studies using both electrical and mechanical stimuli (8,11,25). Thus intermittent sham stimuli with either no current or the same current as in the previous step were given to ensure that the subject did not automatically increase the sensory rating.…”
Section: Stimulation Device and Protocolmentioning
confidence: 99%